Economic Evaluation Protocol and Statistical Analysis Plan for the Cost-Effectiveness of a Novel Australian Stroke Telemedicine Program; the Victorian Stroke Telemedicine (VST) program - Cadilhac, Dominique A.; Sheppard, Lauren; Kim, Joosup; Tan, Elise; Gao, Lan; Sookram, Garveeta; Dewey, Helen M.; Bladin, Christopher F.; Moodie, Marj (Frontiers in Neurology, 2021)
Introduction: Telemedicine can address limited access to medical specialists in rural hospitals. Stroke provides an important case study because: it is a major cause of disease burden; effective treatments to reduce disability (e.g., thrombolysis) can be provided within the initial hours of stroke onset; careful selection of patients is needed by skilled doctors to minimize adverse events from thrombolysis; and there are major treatment gaps (only about half of regional hospitals in Australia provide thrombolysis for stroke). Few economic analyses have been undertaken on telestroke and the majority have been simulation models. The aim of this protocol and statistical analysis plan is to outline the methods for the cost-effectiveness evaluation of a large, multicentre acute stroke telemedicine program being conducted in Victoria, Australia. Methods: Using a historical- and prospective-controlled design, we will compare patient-level data obtained in the 12 months prior to the Victorian Stroke Telemedicine (VST) program implementation and during the first 12 months of VST to determine the incremental difference in costs and patient outcomes at 3 and 12 months. Secondary aims include assessing the cost per additional patient receiving intravenous thrombolysis and the cost per additional patient receiving intravenous thrombolysis within 60 min. Tertiary aims include assessing the potential longer-term cost-effectiveness in the second year of the program at the hospitals to determine whether any program benefits are sustained once site coordinators are no longer employed; and modeling the potential net life-time costs and benefits from a societal perspective. Multivariable uncertainty and one-way sensitivity analyses will be performed to assess the robustness of results. Results: Sixteen hospitals participated. Patient-level data collection including 12-month outcomes for the cohorts obtained in the first and second year of the program for each hospital was completed in January 2020. Conclusion: The results from this real-world study with patient-level data will provide high quality evidence of the costs, health benefits and policy implications of telestroke programs, including the potential for application in other locations within Australia or other countries with similar health system delivery and financing.